Pemanfaatan Digital Forensik dan Teknologi Informasi Dalam Proses Pembuktian Tindak Pidana Pemalsuan Dokumen Elektronik - Edwin Setiawan; Hartiwiningsih Hartiwiningsih (Prosiding Seminar Nasional Ilmu Hukum, 2024)
The rapid development of information technology has brought significant changes, particularly in the area of cybercrime, such as electronic document forgery. This research explores the role of digital forensics and information technology in proving electronic document forgery crimes in Indonesia, using a normative legal research approach. The study employs both a statute approach and a conceptual approach to analyze the effectiveness of digital forensics in uncovering electronic crimes. The findings show that while digital forensics plays a crucial role in investigating electronic document forgery, there are several complex challenges in its implementation. One of the major obstacles is the limited number of certified digital forensic experts in Indonesia, with only 147 professionals qualified in this field. Additionally, the existing legal regulations have not kept pace with the rapid advancements in digital technology, which poses significant challenges to enforcement efforts. The study identifies various technical barriers, such as the complexity of forensic technologies, the volatile nature of digital evidence, and the ever-evolving techniques used by cybercriminals. These factors complicate the process of proving electronic crimes and pose difficulties for investigators. In response to these challenges, the research recommends strategic measures such as strengthening the capacity of forensic laboratories, harmonizing legal regulations with technological advancements, and improving the competency of human resources in both technological and legal fields. The study contributes to the development of a conceptual framework for cyber law enforcement, providing a comprehensive perspective on the challenges faced in proving electronic crimes in the digital age. The research aims to inform policymakers in crafting more effective and adaptive law enforcement strategies.